Incidents of the gender perspective in legal education. An exploratory tour of the legal field in Argentina - Costa Wegsman, Malena (2019)
The 1990s marked a turning point in terms of the impact of the gender category in legal discourse. In Latin America in general, and in Argentina overall, a series of sanctions at the legislative level began to take place since then, all of which have a diverse background. The enactment of these laws is intertwined with other stages of political life, such as the regulations implemented in public institutions and civil services, as well as the claims and many actions carried out throughout a wide range of social movements, political parties and work unions. University and academic education also played a key role in the transformation of the legal field in relation to gender equality and socio-sexual dissidence. Towards the end of the twentieth century, in some study programs of several Latin American universities, the vocabulary linked to gender studies and studies of sexualities is envisioned. In Argentina, the linkage between gender and law begins to emerge as a field of knowledge since the return to democracy in 1983, although it is consolidated during the 1990s and, with greater force, in recent years, based on a variety of events related to the positioning of feminisms in political life.This text submits an exploratory analysis of the incursion of gender and feminist content in the Argentine legal academy. The general purpose is to offer a review on the advances of the so-called gender perspective in university instruction, the political and conceptual complexities that such perspective entails.